Investigation of Prevalence and Awareness of Polycystic Ovary Syndrome among Pakistani Females: Polycystic Ovary Syndrome in Pakistani Women - Zulfiqar, Shumaila; Tahir, Shanzeh; Gulraiz, Sobia; Razzaq, Munnaza Abdul; Abid, Azka; Shahid, Tayyaba; Babar, Aleefia; Rehman, Beenish; Rafique, Huda; Noor, Sufia; Anjum, Iram (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Polycystic ovary syndrome (PCOS) is a polygenic, endocrine disorder causing ovarian dysfunction. This syndrome encompasses a broad spectrum of phenotypic expression due to heterogeneity. This study aimed to investigate the prevalence and phenotypic factors contributing to the onset of PCOS in Pakistani women. Participating females (n=130) were recruited from different regions of Pakistan explicitly those who were trying to conceive for years. We designed a questionnaire having different subsections comprising questions related to psychological and environmental aspects linked with PCOS. We also analyzed the proportion of women having prior awareness about the genetic basis of the disease. The retrieved data was analyzed through SPSS V.21 by employing descriptive statistics. A Chi-square test was used to establish a correlation between PCOS and associated symptoms. Our findings suggest that factors like obesity, facial and abdomen hair growth, irregular periods, menstrual flow, cramps, and hormonal acne corresponds to PCOS in participating females with a p-value (0.000 < 0.05). Around half of the participants were reported to be experiencing one or other symptom related to PCOS from which hirsutism and anxiety were the most common. Furthermore, our findings indicate that multiple psychological and environmental factors contribute to the onset of the disease with a P-Value (0.000 < 0.05). However, a significantly higher p-value (0.247 > 0.05) for excessive hair loss in participants were observed demonstrating that hair loss is not linked with PCOS. In this survey, 46.5 % of participants responded that they know that PCOS can be inherited. 28.5 % of women responded that they had a family history of PCOS. Adopting a healthy lifestyle and maintaining a healthy weight can minimize the severity of PCOS. This survey evaluates different hypotheses which would facilitate a better understanding of the prevalence and associated symptoms of PCOS in Pakistan thereby enabling researchers to develop better diagnostic, management, and treatment strategies for patients.